1992
DOI: 10.1159/000247519
|View full text |Cite
|
Sign up to set email alerts
|

Alopecia areata and lnterleukin-2 Receptor

Abstract: Interleukin-2 (IL-2) is a lymphokine produced by activated T cells and its receptor (IL-2R) is expressed on T cells; one of the IL-2R components can be measured as a soluble serum protein (sIL-2R). Levels of sIL-2R were measured as a sign of T cell activation in serum of 12 patients suffering from alopecia areata (totalis or universalis) and in a group of healthy control subjects. An enzyme-linked immunosorbent assay was used to determine the levels of sIL-2R in blood samples drawn during both the active and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
2
5
0
1
Order By: Relevance
“…In the above study, higher soluble IL-2R levels in PBMC from PAA patients were shown, in agreement with the findings of Valesecchi et al 7 in affected hair follicles. We found significantly increased levels of IL-5 in PAA, also expressing a Th2 response.…”
Section: Reportsupporting
confidence: 92%
“…In the above study, higher soluble IL-2R levels in PBMC from PAA patients were shown, in agreement with the findings of Valesecchi et al 7 in affected hair follicles. We found significantly increased levels of IL-5 in PAA, also expressing a Th2 response.…”
Section: Reportsupporting
confidence: 92%
“…The immune response presented in AA is associated with aberrant lesional expression of interferon-γ, IL-2, and IL-1β, and overexpression of ICAM-1 and major histocompatibility complex molecules on hair follicle keratinocytes and dermal papilla cells [14]. Several clinical and experimental findings point towards IL-2 as a crucial mediator inducing immunologic reaction against human follicle in AA [15, 16]. By using semiquantitative reverse transcription-polymerase chain reaction with RNA extracted from scalp biopsies from patients with AA, Hoffmann et al [17] reported that IL-2 mRNA levels were increased in untreated AT.…”
Section: Discussionmentioning
confidence: 99%
“…Proportionate elevation of sIL-2R serum concentration to illness intensity was observed in diseases such as psoriasis (De Rie et al 1996, Elkayam et al 2000, atopic dermatitis (Colver et al 1989, Gebhardt et al 1997, Halmerbauer et al 1997, Leonardi et al 2004, chronic urticaria (Serhat Inaloz et al 2008), erythema multiformae (Chodorowska et al 2003), pemphigus (Zillikens et al 1993), alopecia areata (Shohat et al 2005, Valsecchi et al 1992) and in nodular erythema (Chodorowska et al 2003). To the best of our knowledge our results are the first on sIL-2R serum concentration in HS patients.…”
Section: Discussionmentioning
confidence: 99%